Study on the Non-equivalent Machining and Error Analysis of Globoidal Indexing Cam - Ge Zhenghao; Liang Chen; Bie Yu; Wang Zhilong (Jixie chuandong)
In terms of improving the processing accuracy and efficiency of globoidal indexing cams,the study on non- equivalent machining is carried out. The non- equivalent processing actual contour surface equation is established by rotating coordinate transformation to deduce and calculate the compensation amount and the compensation direction during the producing progress. Besides,the error is analyzed to through which one processing method would be put into practice to both improve processing efficiency meanwhile reduce processing costs and meet the processing accuracy requirement of globoidal indexing cam.